On the Front Line: Organization of Work in the Information Economy - Pupo, Norene (Labour / Le Travail, 2002)
The article reviews the book, "On the Front Line: Organization of Work in the Information Economy," by Stephen J. Frenkel, Marek Korczynski, Karen A. Shire, and May Tam.